Influence of pH on the anaerobic fluidised bed reactor performance for palm oil mill effluent treatment - Al-Mamun, Abdullah; Idris, Azni; Mujeli, Mustapha (EnPress Publisher, LLC, 2024)
The effect of pH on the performance of a pilot-scale anaerobic fluidised bed reactor (AnFBR) was studied using palm oil mill effluent (POME) as the substrate. The performance of the 2000-litre reactor at different operating conditions, such as organic loading rates and retention times was studied. This acidic agro-industrial wastewater (pH 4.0–5.0) was neutralised by adding slacked lime. It was observed that, within 12 hr of hydraulic retention time (HRT), the AnFBR removes as high as 85% of the substrate chemical oxygen demand (COD) at a loading rate of 4 kg/m3 day. High pre-treatment cost is needed to neutralise the bulk volume of wastewater that was generated from the palm oil industries. Thus, an attempt was made to study the performance of the AnFBR under pH shock load. The influent pH was increased to 9.2 and then dropped around 5.0 to intensify the effect of the pH shock load. At shock load, the reactor performance for COD removal dropped by about 25% lower than the optimum condition. The maximum and minimum COD removal rates during the short period of continuous shock load were 60% and 56.5%, respectively. The average effluent pH remained steady at around 6.1. From the analysis, it was revealed that the anaerobic fluidised bed had the buffering ability and was capable of treating POME with moderate removal efficiency at an influent pH of 5.0